A description of two new species of Ligophorus Euzet & Suriano, 1977 (Monogenea: Ancyrocephalidae) from Malaysian mugilid fish using principal component analysis and numerical taxonomy. Issue 2 (22nd October 2013) - Soo, O.Y.M.; Lim, L.H.S.
Abstract: Ligophorus belanaki n. sp. and Ligophorus kederai n. sp. are described from Liza subviridis Valenciennes, 1836 and Valamugil buchanani Bleeker, 1854, respectively. Ligophorus kederai n. sp. has fenestrated ventral anchors, while in L. belanaki n. sp. the ventral anchor is not fenestrated. Ligophorus belanaki n. sp. is similar to L. careyensis, one of its coexisting congeners, in the overall shape and size of hard parts, but differs in having a flat median piece in the structure of the AMP (antero-median protuberance of the ventral bar), copulatory organ with non-ornamented initial part and longer vaginal tube, compared to raised median piece in the AMP, ornamented initial part and comparatively shorter vaginal tube in L. careyensis . Ligophorus kederai n. sp. is similar to L. fenestrum, a coexisting congener, in having fenestrated ventral anchors, but differs in having longer points and narrower base. Ligophorus fenestrum, unlike L. kederai n. sp., also possesses fenestrated dorsal anchors. The principal component analysis (PCA) scatterplots indicate that the two new and eight known Ligophorus species from Malaysian mugilids can be differentiated based on the morphometries of their anchors, ventral bars and copulatory organ separately and when combined together. Numerical taxonomy (NT) analyses based on Jaccard's Index of Similarity and neighbour-joining clustering, is used to facilitate comparison of these two new species with the 50 known Ligophorus based on morphological and metric characters. The two new species are different from each other and the other 50 species in the overall shapes and sizes of hard parts, as indicated by the NT analyses.